Scoping review of the impact of coronavirus disease 2019 on unplanned pregnancy - Carmen S. Christian; Laura Rossouw (African Journal of Primary Health Care & Family Medicine, 2022)
Background: Increased pressure on the healthcare system because of coronavirus disease 2019 (COVID-19) along with national lockdown policies had consequences on the sexual and reproductive health of women. While the pandemic has resulted in changes in pregnancy intentions, child-bearing and fertility, the direction of this relationship is unclear and is likely to be impacted by each country’s socio-economic status and stage of fertility transition. Understanding the fertility trajectory and the pandemic is important in understanding population structures and ageing, which have consequences for health policies, budgeting and economic activity.